KEWENANGAN LEMBAGA MASYARAKAT ADAT TERHADAP PERSELISIHAN SENGKETA ADAT DI KAMPUNG TOMER, KABUPATEN MERAUKE - Thimon Febby; Nasri Wijaya (Universitas Musamus, Merauke, Papua, 2018)
The purpose of this research is to find out how far the laws and regulations govern the authority of indigenous peoples in resolving customary disputes. The research method used in this study is Sociolegal. This research is a study that looks at law through a combination of normative analysis (legal norms, juridical) and non-legal science approaches. Socio-legal nature is prescriptive Giving solutions to legal problems by combining normative analysis and non-legal approaches / social aspects. The authority between the Marind Imbuti Indigenous Peoples Institution and the Marind Indigenous Peoples Institution Community of Kanum Tomer is the Marind Imbuti Indigenous Peoples Institution having the authority to carry out customary justice for each tribe / community in the disputed indigenous community while the customary community does not have the authority to conduct customary hearings for each member of the tribe disputes but all customary justice mechanisms carried out by the Marind Imbuti Community Institution and the Marind Kanum Indigenous Community as regulated in Article 10 of Perdasus Number 20 of 2008 cannot yet be legally accounted for because they are not in accordance with the instructions of article 10 paragraph (2) of Perdasus Number 20 Year 2008. Keywords: Indigenous Peoples Institutions, Indigenous Disputes